Seedling dynamics of Sorghum halepense (L.) Pers. in wheat. I. Effect of crop density - Tuesca, Daniel; Puricelli, Eduardo; Vitta, Javier I. (Pesquisa Agropecuaria Brasileira, 1995)
This study was undertaken in order to determine the influence of wheat crop on the dynamics of Johnsongrass seedlings and their production of rhizomes and seeds. Trials were conducted during 1988, 1990, and 1992 at Zavalla, Santa Fe, Argentina. Johnsongrass seeds were sown in plots with different wheat densities. Established plants were counted, and at crop harvest dry weight of surviving weed plants was determined. Correlation between weed germination and fluctuating temperatures was observed for all years. Seedling establisliment began during late September and early October. The number of germinated seeds and seedling dynamics was not in agreement with rainfail. Water stress could instead accout for differences in mortality within experiments. Although in wheat systems water conditions are adequate for germination and establisliment of the weed, because of the short growing season and the competition of the crop, it is unlikely that Johnsongrass seedlings could reproduce.